One-Step Synthesis of Hexagonal Boron Nitrides, Their Crystallinity and Biodegradation - Şen, Özlem; Emanet, Melis; Çulha, Mustafa (Frontiers in Bioengineering and Biotechnology, 2018)
Hexagonal boron nitrides (hBNs) have recently been investigated for several novel applications due to their unique properties such as biocompatibility, superhydrophobicity, electrical insulation, and thermal and chemical stability. In addition, their biodegradation products have recently reported to have therapeutic effect on certain cancer types. hBNs are easily synthesized from boron and nitrogen precursors at moderately low temperatures. However, crystallinity and yield vary depending on the type of precursor, reaction temperature, and duration. In this study, a simple one-step hBNs synthesis method is reported without a catalyst, which might be an undesired contaminant for biomedical applications. The influence of boron precursors (boric acid, colemanite, or boron trioxide) on hBNs crystallinity, stability, and biodegradation in suspensions containing oxidative and hydrolytic degradation agents is investigated with the aim of their possible application in biomedicine. We found that the choice of boron precursor is a critically important parameter controlling the hBNs crystallinity and dependently influencing the biodegradation rate.